REHABILITATION AND TRAUMA: THE INTEREST OF THE SCIENTIFIC COMMUNITY (Fiep Bulletin - online, 2013)
The techniques used in rehabilitation aim to re-establish the physical, functional, psychological, social, vocational, avocational and educational potential of patients. A patient with a trauma, probably, should be submitted to a rehabilitation program with a supervision of an interprofessional team. PubMed is a database that is used as a tool in various publications. The aim of this work was to evaluate the number of publications in rehabilitation and trauma using the PubMed. The searches were performed (10/01/2008) in PubMed (http://www.ncbi.nlm.nih.gov/entrez/query.fcgi), from 1949 up to 2008 with the words rehabilitation and trauma. The number of publications was determined in rehabilitation (PRH) and in rehabilitation and trauma (RAT). The total number of citations in each subject was also determined. The percentage of citations to each subject (%PRH and %RAT) was also calculated. The number of publications in rehabilitation was 251594 and in rehabilitation and trauma were 32467. The %PRH has increased from 0.01 (1949) up to 5.91 (2007). Similarly, the %RAT increased from 0.00 (1949) up to 6.54 (2007). Moreover, only 1963 publications in RAT were found. The increase of the %PRH could be related with undesirable conditions (stroke, trauma, amputation, arthritis, orthopedic problems and other related illnesses), as well as with conditions of the Modern Life (stress, malnutrition and pollution). The increase of the %RAT could be related with the increase of the probability of someone undergoes a trauma. In conclusion, the findings reported in this work show the relevance of the PubMed as a tool to evaluate the scientific interest in a specific subject. Furthermore, the increase of publications in rehabilitation could be related with several conditions, as those capable to generate trauma. The presence of an interprofessional team would be very important.
Keywords: rehabilitation; PubMed; scientific community; trauma